Plowshares or swords? End-of-the-world rhetoric in a politically divided world - Brenneman, James E. (Review and expositor, 2023)
A presidential election year, when apocalyptic rhetorical bombast can be at its most cutting and binary, provides an ideal socio-political setting to assess and challenge the standard accounts of political realism. Insofar as appeals to end-of-the-world rhetoric in Scripture are often enough used by politicians backed by their various religious constituencies in making their opposing cases, opposing apocalypses in the Bible provide an ideal literary context to assess and challenge the standard accounts and efforts to unify texts in Scripture that are on-their-face contradictory. Since preachers in pulpits are often the primary interpreters of Scripture to their church-going publics, how might a preacher preach the famous contradictory “plowshare” passages in the Bible (Isa 2:2-4 and Joel 3:9-12) in a season of heightened political tension, indeed, any time when faced with contradictions in the Bible? This article argues for a nonviolent political realism as a political theology for addressing such end-of-the-world binaries that have and continue to threaten real and unleashed violence upon the world.